Parallel Post‐Polyketide Synthase Modification Mechanism Involved in FD‐891 Biosynthesis in Streptomyces graminofaciens A‐8890. Issue 3 (8th January 2016) - Kudo, Fumitaka; Kawamura, Koichi; Furuya, Takashi; Yamanishi, Hiroto; Motegi, Atsushi; Komatsubara, Akiko; Numakura, Mario; Miyanaga, Akimasa; Eguchi, Tadashi
Abstract: To isolate a key polyketide biosynthetic intermediate for the 16‐membered macrolide FD‐891 (1 ), we inactivated two biosynthetic genes coding for post‐polyketide synthase (PKS) modification enzymes: a methyltransferase (GfsG) and a cytochrome P450 (GfsF). Consequently, FD‐892 (2 ), which lacks the epoxide moiety at C8–C9, the hydroxy group at C10, and the O ‐methyl group at O‐25 of FD‐891, was isolated from the gfsF / gfsG double‐knockout mutant. In addition, 25‐ O ‐methyl‐FD‐892 (3 ) and 25‐ O ‐demethyl‐FD‐891 (4 ) were isolated from the gfsF and gfsG mutants, respectively. We also confirmed that GfsG efficiently catalyzes the methylation of2 and4 in vitro. Further, GfsF catalyzed the epoxidation of the double bond at C8‐C9 of2 and3 and subsequent hydroxylation at C10, to afford4 and1, respectively. These results suggest that a parallel post‐PKS modification mechanism is involved in FD‐891 biosynthesis. Abstract : Parallel processing : Two post‐polyketide synthase (PKS) modification enzymes—methyltransferase GfsG and cytochrome P450 monooxygenase GfsF—recognize unique moieties of FD‐892 (the trihydroxyalkyl side chain and the macrocyclic structure, respectively) to complete the biosynthesis of macrolide antibiotic FD‐891.